Chemical control of irrigated rice diseases - Celmer, Alisson; Madalosso, Marcelo Gripa; Debortoli, Mônica Paula; Navarini, Lucas; Balardin, Ricardo Silveiro (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the influence of leaf diseases on the yield of two rice varieties, and to determine the interaction between active ingredients and application stages, for the control of brown leaf spot and oat scald. The products used were: thiofanate methylic, tebuconazole, azoxystrobin and trifloxystrobin + propiconazole, applied in five stages, on the varieties IRGA 417 and El Passo L 144. The parameters observed were disease severity and yield. Chemical control reduced the diseases severity in both cultivars, wich reflected on yield, and was influenced by product e application stage.